2016
DOI: 10.1016/j.jsg.2016.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering viscous flow of frictional melts with the mini-AMS method

Abstract: The anisotropy of magnetic susceptibility (AMS) is widely used to analyze magmatic flow in intrusive igneous bodies including plutons, sills and dikes. This method, owing its success to the rapid nature of measurements, provides a proxy for the orientation of markers with shape anisotropy that flow and align in a viscous medium. AMS specimens typically are 25 mm diameter right cylinders or 20 mm on-aside cubes, representing a volume deemed statistically representative. Here, we present new AMS results, based o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 46 publications
0
16
0
Order By: Relevance
“…A postseismic origin for magnetite can be ruled out for three main reasons: (i) magnetite grains are elongated parallel to the viscous flow fabric of the pseudotachylyte and carry an AMS fabric that is kinematically consistent with coseismic slip, at least in the case of Cima di Gratera (Ferré et al, ); (ii) in contrast to other pseudotachylytes (Ferré, Friedman, et al, and Ferré, Geissman, et al, ), the ultramafic pseudotachylyte veins that we sampled, away from fractures, do not display any color variation from margin to center, a characteristic demonstrating the lack of alteration/serpentinization in our samples; and (iii) the magnetite grains observed in thin section in our samples are not spatially associated with any hydrous phases, which precludes a serpentinization origin (Figure ).…”
Section: Discussionmentioning
confidence: 99%
“…A postseismic origin for magnetite can be ruled out for three main reasons: (i) magnetite grains are elongated parallel to the viscous flow fabric of the pseudotachylyte and carry an AMS fabric that is kinematically consistent with coseismic slip, at least in the case of Cima di Gratera (Ferré et al, ); (ii) in contrast to other pseudotachylytes (Ferré, Friedman, et al, and Ferré, Geissman, et al, ), the ultramafic pseudotachylyte veins that we sampled, away from fractures, do not display any color variation from margin to center, a characteristic demonstrating the lack of alteration/serpentinization in our samples; and (iii) the magnetite grains observed in thin section in our samples are not spatially associated with any hydrous phases, which precludes a serpentinization origin (Figure ).…”
Section: Discussionmentioning
confidence: 99%
“…AMS analysis of pseudotachylyte fabric on such 3.5 mm cubes enabled determining the focal mechanisms of ancient earthquakes (Ferré et al, 2015(Ferré et al, , 2016. Despite sample size issues for very small samples where a cautious and careful interpretation is appropriate, AMS studies on small samples are nonetheless a promising new avenue to unveil detailed geological features (Almqvist et al, 2020;Ferré et al, 2015Ferré et al, , 2016Zhu et al, 2017). Berndt et al (2016) demonstrated that samples with a thermoremanent magnetic moment larger than 10 −11 Am 2 irrespective of their sizes (ranging from the centimeter scale to tens of nm scale) contain enough magnetic particles to be accurate magnetic recorders.…”
Section: Samples For Magnetic Studies Into Fault Rocksmentioning
confidence: 99%
“…AMS fabrics controlled by SPO and/or CPO fabrics may correlate with 3‐D strain, such that principal susceptibility axes ( K 1 ≥ K 2 ≥ K 3 ) and finite strain axes ( X ≥ Y ≥ Z ) are parallel [ Borradaile , ; Borradaile and Jackson , ; Kruckenberg et al ., , ; Ferré et al ., , ]. Correlations may also exist between P ′ and finite strain magnitude [e.g., Benn , ; Tripathy , ] and between T and strain geometry [e.g., Sidman et al ., ].…”
Section: Anisotropy Of Magnetic Susceptibility (Ams)mentioning
confidence: 99%